Rapid and reliable identification of Staphylococcus aureus by a latex agglutination test. - Essers, L (1980)
A latex slide agglutination test detecting clumping factor and protein A simultaneously is recommended for rapid and reliable routine identification of Staphylococcus aureus. Strains (836) of staphylococci isolated from clinical specimens were examined, all S. aureus strains identified by conventional methods were correctly differentiated by the latex test, and no false-positive results occurred with other staphylococci. The reagent is easy to prepare since plasma is the coating material.